Exchange rates, global value chains, market structure and trade restrictions as determinants of international prices - Firanchuk, Aleksandr (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2021)
This dissertation addresses questions in the areas of exchange rate pass-through into international prices. It examines the effect of strategic competition in the destination market and the use of foreign inputs in production on the degree of export price adjustment following exchange rate shocks. It also discusses how to separate the effects of two factors affecting import prices: a partial import ban and an importer currency depreciation. Chapter 1 analyses how foreign inputs embodied in gross exports and an exporting country size affect the degree of exchange rate pass-through. An oligopolistic competition model, where firms use foreign inputs in production, makes two predictions: (i) the use of foreign inputs reduces export price reaction to exchange rate movements and (ii) an exporting country share in a destination market increases it. I test the hypotheses for 57 economies over the period 2000-15. For trade between advanced economies, imported inputs reduce pass-through, but only in the case of producer currency movements; for trade with emerging markets, the evidence is weaker. Chapter 2 considers the determinants of the exchange rate pass-through into export prices for the EU members with floating national currencies. These are clear-cut examples of small open economies for which the euro -- neither a producer nor an importer currency -- plays a dominant role. I find that the degree of export price adjustment is asymmetric: it is much higher when an importer currency moves against the euro than in the case a producer currency does. Applying the oligopolistic competition model where a bilateral exchange rate is explicitly decomposed into a producer currency component and a local currency one, I show that imported inputs and firms' strategic competition are sources of the asymmetry. I empirically investigate both channels and quantify their contribution to this asymmetry. Chapter 3 considers Russia s import ban of certain foodstuffs and agricultural products from the EU, US and some other states imposed in August 2014. The ban implementation coincided with the period of a substantial depreciation of the Russian ruble. Before the ban, the target countries' share in Russia's import and total consumption varied across product groups in a wide range. Exploiting that heterogeneity, I disentangle the ban's influence on prices from the depreciation's one. The results show that the ban effect on import and consumer prices increased in the second half of 2014, then gradually declined, disappearing by the end of 2015.
APPROVED
Keywords: international trade; exchange rate pass-through; global value chains; market structure; export prices; import prices; consumer prices; the European Union; Russia; trade sanctions